2004
DOI: 10.1016/j.icarus.2004.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Jovian auroral spectroscopy with FUSE: analysis of self-absorption and implications for electron precipitation

Abstract: High-resolution (∼ 0.22 Å) spectra of the north jovian aurora were obtained in the 905-1180 Å window with the Far Ultraviolet Spectroscopic Explorer (FUSE) on October 28, 2000. The FUSE instrument resolves the rotational structure of the H 2 spectra and the spectral range allows the study of self-absorption. Below 1100 Å, transitions connecting to the v 2 levels of the H 2 ground state are partially or totally absorbed by the overlying H 2 molecules. The FUSE spectra provide information on the overlying H 2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 33 publications
4
58
0
Order By: Relevance
“…It is shown that the conductance at this current is P ≈4 mho with small variation on the spectra, whereas the conductance in the other two cases is smaller by a factor of 2. This may be due to the effect of the low energy component of spectra in Grodent et al (2001) and Gustin et al (2004) to reproduce observed high atmospheric temperature. Assuming that the low energy component cannot reach the peak altitude of ion mobility, we try to eliminate the component from the definition of current j .…”
Section: Discussion On Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the conductance at this current is P ≈4 mho with small variation on the spectra, whereas the conductance in the other two cases is smaller by a factor of 2. This may be due to the effect of the low energy component of spectra in Grodent et al (2001) and Gustin et al (2004) to reproduce observed high atmospheric temperature. Assuming that the low energy component cannot reach the peak altitude of ion mobility, we try to eliminate the component from the definition of current j .…”
Section: Discussion On Conductancementioning
confidence: 99%
“…11a, b). Furthermore, we adopt two flux functions derived on the basis of observation results (Grodent et al, 2001;Gustin et al, 2004), with a simple normalization of these magnitudes to adjust j . Variations in the conductance through spectral configurations are shown in Fig.…”
Section: Discussion On Conductancementioning
confidence: 99%
“…observations with the Far Ultraviolet Spectroscopic Explorer by Gustin et al 2004b). Such former spectroscopic observations thus do not allow us to draw a global picture of the processes responsible for polar auroras.…”
Section: Objectives Of the Studymentioning
confidence: 98%
“…These images were obtained by integrating the spectrum corresponding to each spatial pixel in the 1550-1620 Å bandwidth, unaffected by hydrocarbon absorption, and multiplied by 8.1 to extend the result over the whole UV. The latter factor has been determined from a synthetic H 2 spectrum as 235 described by Gustin et al (2004b). All brightnesses mentioned hereafter correspond to unabsorbed emission for the whole UV bandwidth.…”
mentioning
confidence: 99%
“…Far from the Galileo probe descent region and the Voyager occultation latitudes, the temperature profile is uncertain apart from scattered values obtained indirectly through H + 3 or H 2 vibrational emissions, etc. (Grodent et al, 2001;Gustin et al, 2004;Raynaud et al, 2004;etc. ).…”
Section: Temperature Gradient Of Thermospherementioning
confidence: 99%